IDENTIFICATION OF LEAD AND CADMIUM LEVELS IN WHITE CABBAGE (Brassica rapa L.), SOIL, AND IRRIGATION WATER OF URBAN AGRICULTURAL SITES IN THE PHILIPPINES - ., Hardiyanto; De Guzman, Constancio C. (Indonesian Agency for Agricultural Research and Development - MOA, 2008)
Urban agriculture comprises a variety of farming systems,ranging from subsistence to fully commercialized agriculture.Pollution from automobile exhaust, industrial and commercialactivities may affect humans, crops, soil, and water in and aroundurban agriculture areas. The research aimed to investigate thelevel and distribution of lead (Pb) and cadmium (Cd) in whitecabbage (Brassica rapa L.), soil, and irrigation water taken fromurban sites. The research was conducted in Las PiÃ±as andParaÃ±aque, Metro Manila, Philippines. The field area was dividedinto three sections based on its distance from the main road(0, 25, and 50 m). Irrigation water was taken from canal (LasPiÃ±as) and river (ParaÃ±aque). Pb and Cd contents of the extractwere measured by Atomic Absorption Spectrophotometry. Combinedanalysis over locations was used. The relationshipbetween distance from the main road and metal contents wasmeasured by Pearsonâs correlation. Based on combined analyses,highly significant difference over locations was only showedon Cd content in white cabbage. Cd content in white cabbagegrown in ParaÃ±aque was higher than that cultivated in Las PiÃ±as,while Cd content in the soil between both sites was comparable.The average Pb content (1.09 Âµg g-1 dry weight) was highest inthe white cabbage grown right beside the main road. A similartrend was also observed in the soil, with the highest concentrationbeing recorded at 26 Âµg g-1 dry weight. There was a negativerelationship between distance from the main road and Pb andCd contents in white cabbage and the soil. Level of Pb in watertaken from the canal and river was similar (0.12 mg l-1), whereaslevels of Cd were 0.0084 and 0.0095 mg l-1, respectively. Ingeneral, the concentrations of Pb and Cd in white cabbage andsoil as well as irrigation water were still in the acceptable limits.In terms of environmental hazards and polluted city environment,it seems that big cities in Indonesia especially Jakarta andSurabaya have the same problem with the Philippines. Therefore,it is suggested that the study on heavy metal contaminationin several crops, especially those grown along the mainroad, should be conducted.